Latent deleterious effects of binge drinking over a short period of time revealed only by electrophysiological measures - Maurage, Pierre (Canadian Medical Association, 2009)
BACKGROUND: Episodic excessive alcohol consumption (i.e., binge drinking) is now considered to be a major public health problem, but whereas short-and long-term harmful consequences of this behaviour are clearly established at medical, social and cognitive levels, the cerebral correlates of these impairments are still unknown. Our study explores the midterm cerebral effects of binge-drinking behaviours among young adults. METHODS: We selected 2 groups of first-year university students with no history of drinking habits, paired for psychological and behavioural measures on the basis of their expected alcohol consumption during the forthcoming academic year. The binge drinker group expected to have high personal alcohol consumption, whereas the control group expected low consumption. We used a test–retest paradigm within a 9-month period (session 1 in September 2005, session 2 in May 2006). At each testing session, we recorded auditory event-related potentials while the participants performed an emotional valence judgment task. RESULTS: There were no differences between the groups in behavioural or electrophysiological measures at baseline. After 9 months, the binge drinkers had significantly delayed latencies for all event-related potential components (P1, N2, P3b) of emotional auditory processing compared with the control group (p < 0.006), with no behavioural differences. LIMITATIONS: As the present study explored the electrophysiological correlates of binge drinking with an emotional task only, the results will have to be extended to other cognitive processes using various experimental tasks. CONCLUSION: We report the first direct evidence that short-term binge drinking can produce marked cerebral dysfunction undetectable by behavioural measures alone. The observed latency abnormalities, similar to those observed in long-term alcoholism, constitute an electrophysiological marker of slowed cerebral activity associated with binge drinking.